A genetically informed examination of posttraumatic stress disorder and traumatic brain injury's impact on dementia risk in US Veterans. (20th December 2022) - Logue, Mark W.; Sherva, Richard; Zhang, Rui; Harrington, Kelly; Fonda, Jennifer; Merritt, Victoria; Panizzon, Matthew S.; Hauger, Richard L.; Wolf, Erika; Miller, Mark
Abstract: Background: The US Veteran population is aging, and Veterans have higher rates of dementia risk factors such posttraumatic stress disorder (PTSD) and traumatic brain injury (TBI). Moreover, some studies have indicated that APOE :ε4 (the largest Alzheimer's disease genetic risk factor) x TBI interactions could further elevate dementia risk. Method: Alzheimer's disease and related dementia (ADRD) risk was examined using the electronic medical record and survey‐based phenotypes in the VA Million Veteran Program (MVP) cohort. We examined the impact of TBI (survey‐based), PTSD (medical record and survey‐based), and APOE :ε4 on ADRD risk in a European‐descent cohort (EUR, n=11, 112 ADRD cases; 170, 361 controls) and an African American cohort (AA, n=1, 443 ADRD cases; 16, 191 controls). Result: PTSD, TBI, and ε4 were associated with ADRD in both cohorts (p<10 ‐9 ). In EUR, logistic models indicated dementia risk associated with TBI (OR=1.96) was approximately that of ε4 (OR=2.05), while the PTSD‐associated risk was slightly higher (OR=2.18). In AA, the effect of PTSD and ε4 were similar (OR=1.73 and 1.69 respectively), while the effect of TBI was higher (OR=2.69). GxE analyses yielded a modest but significant PTSD x ε4 interaction term in EUR (OR=0.84, p=0.0046). As multiplicative (logistic) interactions can be difficult to interpret, we calculated the risk curves predicted by the models (Figure 1) and relative excess risk due to interaction (RERI), which measures additive‐scale interactions. Modest but significant positive RERIs were observed for PTSD x APOE (EUR, RERI=1.28) and TBI x APOE (EUR and AA, RERI=0.86 and 1.45 respectively), indicating that risk of ADRD in terms of raw percentage associated with PTSD/TBI case status increases as ε4 dosage increases. For example, age 80 risk of ADRD associated with PTSD (PTSD case ADRD% – control ADRD%) in EUR is predicted to be 5.70% for those with one copy of ε4 and 11.19% for two copies of ε4. Conclusion: Although the mechanisms have yet to be elucidated, PTSD, TBI, and genetic risk are strongly associated with dementia in Veterans. Veterans with PTSD and TBI have increased risk for ADRD and require monitoring for early detection of cognitive decline which can precede dementia onset.